Pengaruh Mobile Banking, Size Perusahaan, Risiko Kredit Terhadap Kinerja Keuangan Perbankan Indonesia: Studi Kasus pada Perusahaan Perbankan Konvensional yang Terdaftar di Bursa Efek Indonesia Tahun 2016 - 2020 - Joshua Caturputra Thio; Meina Wulansari Yusniar (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The purpose of this study is to analyze the effect of mobile banking, company’s size and credit risk on the financial performance of Indonesian banks based on Return on Assets (ROA), Return on Equity (ROE) and Operating Costs to Operating Income (BOPO) in banking companies listed on the Indonesia Stock Exchange in 2016 – 2020. The type of research used is explanatory research, with the unit of analysis in this study covering research variables consisting of Mobile Banking, company size and Credit risk or Non Performing Loan (NPL) as independent variables, Return on Assets, Return on Equity and Operating Costs to Operating Income as the dependent variable, which is obtained from the financial statements of banks listed on the Indonesia Stock Exchange for the period 2016 – 2020. The sample of this research is 20 banks. The analytical techniques used in this study are path analysis and multiple regression analysis. The results of the study indicate that mobile banking has no significant effect on the financial performance of Indonesian banks. The other independent variables measured using firm size and NPL have a significant effect on the financial performance of Indonesian banks which are measured using ROA, ROE, BOPO.